Intranasal mucoadhesivemicroemulsion for neuroprotective effect of curcuminin mptp induced Parkinson model (Brazilian Journal of Pharmaceutical Sciences, 2017)
This study was to investigate the neuroprotective effect of curcumin against inflammation-mediated dopaminergic neurodegeneration in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mice model of Parkinson's disease (PD). Curcumin loaded sodium hyaluronate based mucoadhesive microemulsion (CMME) was developed by using Box Behnken design of Response surface method (RSM) and was characterized. Male C57BL/6 mice were first treated with four intraperitoneal injections of MPTP (20 mg/kg of body weight) at 2 h intervals followed CMME intranasal administration for 14 days at 2.86 mg of curcumin/kg of body weight per once a day. Optimal CMME containing 3% Capmul MCM as oil phase, 37 % of Accenon CC and Transcutol HP at 2.5:1 ratio and 0.5% sodium hyaluronate was stable, non-ciliotoxic with 57.66 nm±3.46 as average globule size. PdI value (0.190 ± 0.19) and TEM result depicted the narrow size distribution of CMME.All three independent variables had a significant effect (p